The Effect of Business Ethics Principles on Operational Budget Control Policy (Cost Transport) - Alamsyah Alamsyah; Indrianty Sudirman; Wardhani Hakim (Hasanuddin Journal of Business Strategy, 2020)
The research aimed to determine the effect of business ethics on budgeting control at PT. Patra Niaga (PT. PN). The research used a quantitative approach by basing a rational principle study. The analysis was carried out using the regression method and processed using SPSS 22. Data from permanent employees of PT. PN was determined based on proportional sampling. A total of 30 respondents. Data collection used questionnaires as the main instrument, interviews, and observations. The results showed that the autonomy principle, the honesty principle, the justice principle, and the mutual benefit principles have a positive and significant effect on budgetary control at the office of PT. PN. Interestingly, the justice variable is the most dominant positive and significant effect on budget control at the office of PT. PN.